Effect of Stocking Density on the Survival Rate and Growth Performance in Penaeus monodon - C. Shakir; A.P. Lipton; A. Manilal; S. Sugathan; J. Selvin (Journal of Basic & Applied Sciences, 2014)
In this study, effect of stocking density and water exchange rate on the survival, growth and apparent feed conversion ratio of Penaeus monodon were evaluated. For that, shrimps were cultured at two different stocking densities such as six and twelve post larvae m?3 for a period of four months. The experimental ponds were harvested after four months of culture. The results revealed that survival rate of shrimps cultured in low density ponds (LD) was higher (68.4%) whereas a lower rate (51.7%) was observed at high density ponds (HD). In the case of average body weight and length, the shrimps reared at LD experimental ponds were 27.8 g and 18.5 cm respectively. In addition, the average FCR value of shrimps reared at LD ponds was higher (1.8) when compared to the shrimps cultured in HD ponds (2.3). Therefore, stocking density of 6 PL/m3 is recommend for culturing P. monodon in Kollam coast of India under these experimental conditions.